The Implementation of Green Accounting in Indonesia: A Bibliometric Analysis - Muhammad Nur; Molina; Erwin Indriyanto; Kumba Digdowiseiso; Hafiza Aishah Hashim (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The implementation of Green Accounting has become an important topic in academic literature. Indonesia, as a country with significant environmental challenges, increasingly supports this initiative. This study aims to analyze the development of Green Accounting research in Indonesia. Bibliometric data were obtained from Google Scholar for articles published between 2017 and 2023. The analysis involved the use of VOS Viewer to depict research networks, distribution of articles, and citations in time. The results show a growing trend in Green Accounting research in Indonesia. However, company awareness of its implementation is still low. Trends show an increase in the number of articles and citations until 2018, but a decline thereafter. Major journal distributions include Elsevier, mdpi.com, and emerald.com. The implementation of Green Accounting in Indonesia faces obstacles, especially in efforts to balance economic and environmental development. These research trends are evolving, although implementation challenges remain apparent. This provides important insight into efforts to encourage understanding and awareness of the role of Green Accounting in achieving sustainable development in Indonesia.